Computer support for diagnostic teaching – the case of decimal numbers - Fuglestad , Anne Berit (NOMAD Nordic Studies in Mathematics Education, 1998)
Computers with different kinds of software were used in mathematics teaching during one school year with Norwegian students of age 10–14. The development of students’ understanding of decimal numbers was investigated, using computers to support a diagnostic teaching approach. In particular some spreadsheet tasks were used to stimulate mathematical investigations and to generate discussions exhibiting conflict. An item analysis of pre-test data revealed a common pattern of misconceptions on decimal numbers. As the students worked on the spreadsheet tasks, their concepts seemingly were in conflict with what they observed. This led the students into lively discussions. The test results indicated that the computer group improved significantly by comparison with the control group on part of the test, with the greatest improvement from the ’high’ spreadsheet users in the research group.